Simulation study of front-illuminated GaN avalanche photodiodes with hole-initiated multiplication. Issue 1 (1st January 2020) - Wang, Yangqian; Zhang, Yuliang; Yang, Yang A.; Lu, Xing; Zou, Xinbo
Abstract: A flip-chip GaN p-i-n-i-n avalanche photodiode (APD) which integrates the merits of the prevailing APDs—hole-initiated multiplication process and front-illumination is proposed and studied via simulation. The simulation parameters used were firstly calibrated with a fabricated PiN diode. With a 200-nm-thick multiplication layer in the flip-chip GaN p-i-n-i-n diode, the calculated breakdown voltage was around 75 V and the optical gain could reach 10 5 . Geiger-mode APDs were demonstrated using two quenching schemes. With a passive resistive quenching circuit, it took about 30 μs to finish the current quenching and voltage reset process. While by adding an n-MOSFET device to form an active quenching circuit, the current quenching process was significantly accelerated and the dead time was reduced to be dozens of nanoseconds only.